Covid-19 Pandemic: Impact on Economic Stability In 8-Em Muslim Countries - Lia Nazliana Nasution; Suhendi Suhendi; Rusiadi Rusiadi; Dewi Mahrani Rangkuty; Abdiyanto Abdiyanto (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2022)
The impact of the COVID-19 epidemic on economic stability in 8-EM muslim countries is enormous. The analysis forecasts how big of an impact it will have on the extent of the economic recession in the eight EM Muslim countries. The ARDL Panel is utilized in the data analysis model and the independent sample t-test model. As a result, the money supply flowing from all eight EM Muslim nations has a greater impact on economic stability and recession in Indonesia than it does in Saudi Arabia or Pakistan. Muslim emerging market countries that are very capable of controlling macroeconomic stability during the Covid-19 pandemic are Bangladesh, Indonesia with variable government expenditures, taxes, interest rates, money supply then Malaysia through tax policies and government expenditures, investment and money supply, UAE and Saudi Arabia policies stabilize the economy on tax variables, investments, money supply, Egypt and Turkey through money supply. Indonesia has the ability to control the economy through exchange rates. Bangladesh and Malaysia through the money supply. These results suggest that economic stability must be controlled hammering control over the money supply and exchange rate.